2006
DOI: 10.1002/ejlt.200600006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of storage and grilling on fatty acids in muscle of pigs fed plant oils

Abstract: The purpose of the study was to assess changes in the fatty acid composition of raw and grilled pig muscles after different storage periods. A total of 13 female and 12 castrated Pietrain×German Landrace pigs were fed a basal concentrate diet supplemented with 5% olive oil or 5% linseed oil during the growing‐finishing period. An entire cut of the pork loin with bone (15th rib to 5th lumbar vertebra) was stored at 5 °C for 48, 96 or 144 h. Simultaneous analyses of intramuscular fat and lipid composition were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…These results are consistent with those obtained for the same amino acids in beef (Greenwood et al, 1951), pork and lamb cuts (Schweigert et al, 1949). The literature mainly describes the fatty acid composition of fresh meat from meat producing animals (Nuernberg et al, 2006). The effect of cooking on fatty acid composition of meat has been reported with contradictory results due to different animal species, meat cuts, cooking methods and temperatures ( Janicki and Appledorf, 1974;Ono et al, 1985;Slover et al, 1987;Smith et al, 1989;Heymann et al, 1990;Zirpin and Rhee, 1990;Scheeder et al, 2001, Sarries et al, 2009, Gerber et al, 2009.…”
Section: Resultsmentioning
confidence: 99%
“…These results are consistent with those obtained for the same amino acids in beef (Greenwood et al, 1951), pork and lamb cuts (Schweigert et al, 1949). The literature mainly describes the fatty acid composition of fresh meat from meat producing animals (Nuernberg et al, 2006). The effect of cooking on fatty acid composition of meat has been reported with contradictory results due to different animal species, meat cuts, cooking methods and temperatures ( Janicki and Appledorf, 1974;Ono et al, 1985;Slover et al, 1987;Smith et al, 1989;Heymann et al, 1990;Zirpin and Rhee, 1990;Scheeder et al, 2001, Sarries et al, 2009, Gerber et al, 2009.…”
Section: Resultsmentioning
confidence: 99%
“…Meat color is regarded as an indicator for evaluating meat quality in broilers which myoglobin level, type of muscle, pH, as well as broiler age at slaughter are effective factors on it. 22 In this experiment, addition of silicate minerals to broiler dietary were effective in improving meat quality characteristics during storage (Figure 1 and 2). It reported that there is a reverse relation between the amount of dietary protein and level of intramuscular fat; further, a direct positive relation seen between dietary energy level and the amount of intramuscular fat indicating that the more intramuscular fat much higher lipid oxidation.…”
Section: Discussionmentioning
confidence: 76%
“…It reported that there is a reverse relation between the amount of dietary protein and level of intramuscular fat; further, a direct positive relation seen between dietary energy level and the amount of intramuscular fat indicating that the more intramuscular fat much higher lipid oxidation. 22,23 Our previous studies revealed that adding silicate minerals in broiler dietary may lead to a significant increase in the protein digestibility; while, it showed no significant effect on energy digestibility. 24 Moreover, inclusion silicate minerals to diets may increase meat protein amount and reduce intramuscular fat and abdominal fat in broilers chickens.…”
Section: Discussionmentioning
confidence: 99%
“…Decreases in TBA values have also been observed in meat lipids after the culinary treatment of the pieces of dry-cured forelegs (Cobos et al, 2008), after boiling beef muscles (Badiani et al, 2002) and after grilling pork muscles (Nuernberg et al, 2006). The explanation of these results might be the degradation or denaturation of aldehydes that make the TBA-reactive substances less assessable for measurement (Nuernberg et al, 2006).…”
Section: Chemical and Lipid Compositionmentioning
confidence: 88%